Prevalence of Methicillin-resistant Staphylococcus aureus Carrying lukS-lukF Gene in Iraqi Patients with Furunculosis - Al-Halaq, Abdlhafed Abdlhalem Ismael; Utba, Nawal M. (Iraqi Journal of Science, 2023)
In this study, Staphylococcus aureus was found to be the causative agent of furunculosis in 64 (27.5%) out of 233 Iraqi patients presented with furunculosis. 16SrRNA gene was located in all isolates. Nevertheless, mecA and lukS-lukF genes were located in 60% and 4% of S. aureus isolates, respectively. Interestingly, the lukS-lukF carrying S. aureus isolates were mecA positive as well.